Analysis of the impact of fundamental reports on the price of selected financial instruments - Strnad, David; Fičura, Milan; Babusik, Martin; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2024)
The main objective of this thesis was to investigate the potential impact of periodically published reports on the prices of selected precious and industrial metals. After an overview of the current understanding of this topic as well as of methods used in studies with similar aims was conducted, an empirical analysis was conducted. For empirical analysis of data from 2008 to 2023, linear regression was used in the approach utilising the surprise effect of the report’s publication as a predictor and in the approach utilizing returns from the report’s publication day. While the predictors significantly explain the various future returns of selected metals in both approaches, the out-of-sample testing confirms that most of these returns are not significantly different from zero.
Vedoucí práce: Milan Fičura
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: finanční inženýrství [obor dipl. práce]; diplomové práce; master's theses